Development and Optimization of a Stable Parenteral Formulation of Relugolix to Overcome Oral Bioavailability Limitations in the Management of Prostate Cancer - Priyanka Nagar; Robin Kumar; Shilpa Chaudhary; Amit Kamboj; Minakshi Garg (Journal of Pharmaceutical Innovation, 2027)

Genetic dissection of maydis leaf blight resistance in maize through QTL mapping - Bhupender Kumar; Rakhi Singh; Shrikant Yankanchi; Pardeep Kumar; Pushpendra Pushpendra; Pravin Bagaria; Robin Gogoi; Prahlad Piyal; Neelam Sunil; Ajay Kumar (Molecular Biology Reports, 2026)

Aflatoxins: global insights on occurrence, health risks, regulations, and integrated management strategies from farm-to-fork for a safer food system - Aashish Kumar Sharma; Robin Rijal; Adesh Kumar; Bijaya Bagale (Food Control, 2026)

The salivary gland transcriptome of tick Rhipicephalus microplus shaped by the genetic composition of host - Nyumpi Bagra; Upalabdha Dey; Anupam Dutta; Daniel Mize; Aditya Kumar; Rupak Mukhopadhyay; Robin Doley (Veterinary Parasitology, 2026)

Technical note: Correction factors for instruments used in periodic technical inspection of diesel vehicles - Konstantina Vasilatou; Nicola Kramer; Kevin Auderset; Loïc Gurtner; Markus Knoll; Mark de Goede; Barouch Giechaskiel; Max Griffig; Ashish Kumar; Partik Chavda; Stephan Grosse; Daniel Göhler; et al. (Journal of Aerosol Science, 2026)

Volatilome-functionalized biopolymer coating for postharvest anthracnose management and shelf life extension in banana - Misha Poddar; Alexander Balamurugan; Brijesh Kumar Yadav; Krishnan Sakthivel; Eldho Varghese; Aditi Kundu; Robin Gogoi; Charanjit Kaur; Aundy Kumar (Indian Phytopathology, 2026)

Nutritional benefits and post-harvest management of large cardamom (Amomum subulatum roxb): A review - Robin Subba; Rakesh Kumar Raigar (Food and Humanity, 2026)

Elevating Drug Safety Oversight: A Comprehensive Examination of Dynamic and Static Monitoring Systems across the United States, European Union, and India - Deepika N; Robin George; Ravi Kumar Reddy Juturi; Baharul Islam Haidary; Prasiddhi Naik; Prakash Goudanavar (Journal of Pharmaceutical Innovation, 2026)

Zero mortality in 2024: Retrospective assessment of snakebite cases and their effective management at Demow rural community health centre, Sivasagar, Assam, India - Amit Talukdar; Prasenjit Roy; Jayaditya Purkayastha; Simanta Jyoti Taye; Deepak Agarwalla; Ruma Shyam; Hridoy Baruah; Rentu Kumar Gam; Gaurav Choudhary; Rajib Jangid; Anurag Borthakur; Surajit Giri; et al. (Toxicon, 2025)

Genome sequence of Bipolaris maydis inciting maydis leaf blight provides insights into genome architecture and putative effector repertoire - Poulami Basak; Malkhan Singh Gurjar; Tej Pratap Jitender Kumar; Natasha Kashyap; Sri Ananth Kurella; Muthyala Mahendra; Rahul Patidar; Sangale Smita; Kartiki Sharma; Robin Gogoi (Physiological and Molecular Plant Pathology, 2025)

Malnutrition induces steatohepatitis by impairing hepatic lipid metabolism, mitochondrial function and the gut-liver axis - Vinesh Sharma; Raman Kumar; Robin Joshi; Vidyashankar Srivatsan; Vikram Patial (Journal of Physiology and Biochemistry, 2025)

Improving liver cancer diagnosis: A multifaceted approach to automated liver tumor identification in ultrasound scans - B.P. Pradeep kumar; Pramod∼K.∼B. Rangaiah; Robin Augustine (Next Research, 2025)

Exploring the endophytic microbiome of maize leaves: roles in plant growth promotion and defense against Bipolaris maydis - Sudeepta Pattanayak; Vinod Chouhan; Bishnu Maya Bashyal; Pranab Kumar Mandal; Mohit Kumar; Robin Gogoi; Aundy Kumar (Plant and Soil, 2025)

Associations of anthropogenic activity and tributaries with the physicochemical, nutrient and microbial composition of the Ganga (Ganges) River, India - Gillian E. Clayton; Laura A. Richards; Bethany G. Fox; Robin M.S. Thorn; Michael J. Bowes; Daniel S. Read; Holly J. Tipper; Kieran Khamis; Tapan K. Dutta; Arun Kumar; Moushumi Hazra; Ben Howard; et al. (Water Research, 2025)

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Copper-based nanoformulation stimulates host defense response in maize against Bipolaris maydis - Lham Dorjee; Robin Gogoi; Deeba Kamil; Rajesh Kumar; Bishnu Maya Bashyal; Tapan Kumar Mondal; Bishal Gurung (Indian Phytopathology, 2025)

Differential role of endogenous hormones and effect of exogenous hormonal-temperature treatments on seed dormancy and germination in Heeng (F. assa-foetida L.) and its wild relative F. jaeschkeana Vatke - Ravi Kumar; Amit Rana; Pawan Kumar; Shimran Yadav; Robin Joshi; Dinesh Kumar; Satbeer Singh; Ramesh Chauhan; Sanatsujat Singh; Ashok Kumar (South African Journal of Botany, 2025)

Bioprospecting of bacterial endophytes from Solanum pimpinellifolium with antifungal activity against Fusarium oxysporum f.sp. lycopersici causing vascular wilt - Bandana Saikia; Ashok Bhattacharyya; Robin Chandra Boro; Ajit Kumar Savani; Bhuvaneswari V (Physiological and Molecular Plant Pathology, 2025)

Evidence-base for urban green-blue infrastructure to support insect diversity - Diana E. Bowler; Corey T. Callaghan; Jéssica F. Felappi; Brittany M. Mason; Robin Hutchinson; Prashant Kumar; Laurence Jones (Urban Ecosystems, 2025)
Green-blue urban infrastructures potentially offer win-win benefits for people and nature in urban areas. Given increasing evidence of widespread declines of insects, as well as their ecological importance, there is a need to better understand the potential role of green-blue urban infrastructure for insect conservation. In this review, we evaluated 201 studies about the ability of green-blue infrastructure to support insect diversity. Most studies were focused on the role of local and landscape-level characteristics of green-blue infrastructure. Fewer studies explicitly compared one type of infrastructure to another, and even fewer compared insect communities between green-blue infrastructure and traditional infrastructure. Overall, the body of research highlights the importance of plant diversity and reduced intensity of management (e.g., mowing) for most insect taxon groups. While local characteristics seem to be generally more important than landscape factors, insect communities within green-blue infrastructures can also depend on their connectivity and landscape context. Some infrastructure types are generally more beneficial than others; for instance, ground-level habitats tend to support more insects than green roofs. Few studies simultaneously studied synergies or trade-offs with other services provided by green-blue infrastructure, but environmental variables, such as tree cover and plant diversity, that affect insects are likely to also affect the provision of other services such as improving thermal comfort and the well-being of people. Our review offers some initial evidence for how green-blue infrastructure could be designed for multifunctionality with insects in mind.

Evidence of a Proterozoic suture along the southern part of Eastern Ghats Mobile Belt: Implications for the Nuna supercontinent - Yellalacheruvu Giri; M Radhakrishna; Peter Betts; T K Biswal; Robin Armit; Sumanta Kumar Sathapathy; P U Naveen (Journal of Earth System Science, 2024)

Correction to: Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)

Biodegradable Schiff bases: a novel approach for the management of pathogenic fungi (Sclerotium rolfsii and Rhizoctonia bataticola) and stored grain insect (Callosobruchus maculatus) in green gram (Vigna radiata) - Tilak Mondal; Rajesh Kumar; Jeevan Bettanayaka; Robin Gogoi; Prasanna Koti; Mrinmoy Ray; Ramen Kumar Kole; Santanu Mukherjee (Environmental Science and Pollution Research, 2024)

The RESIST Senior Individuals Cohort: Design, participant characteristics and aims - Lennart Matthias Roesner; Manoj Kumar Gupta; Verena Kopfnagel; Nienke van Unen; Yvonne Kemmling; Jana-Kristin Heise; Stephanie Castell; Xun Jiang; Lennart Riemann; Stephan Traidl; Berit Lange; Kurt-Wolfram Sühs; et al. (GeroScience, 2024)
The number of older adults worldwide is growing exponentially. However, while living longer, older individuals are more susceptible to both non-infectious and infectious diseases, at least in part due to alterations of the immune system. Here, we report on a prospective cohort study investigating the influence of age on immune responses and susceptibility to infection. The RESIST Senior Individuals (SI) cohort was established as a general population cohort with a focus on the elderly, enrolling an age- and sex-stratified sample of 650 individuals ( n = 100 20-39y, n = 550 61-94y, 2019–2023, Hannover, Germany). It includes clinical, demographic, and lifestyle data and also extensive biomaterial sampling. Initial insights indicate that the SI cohort exhibits characteristics of the aging immune system and the associated susceptibility to infection, thereby providing a suitable platform for the decoding of age-related alterations of the immune system and unraveling the molecular mechanisms underlying the impaired immune responsiveness in aging populations by exploring comprehensive, unbiased multi-omics datasets.

Characterizing genetic diversity of Sclerotium rolfsii isolates by biomapping of mycelial compatibility groupings and multilocus sequence analysis - C. Shanmugaraj; Deeba Kamil; Robin Gogoi; Amrita Das; G. M. Sandeep Kumar; Zakir Hussain; Praveen Kumar Singh; M. A. Iquebal (World Journal of Microbiology and Biotechnology, 2024)

Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)
Immunogenicity testing and characterization is an important part of understanding the immune response to administration of a protein therapeutic. Neutralizing antibody (NAb) assays are used to characterize a positive anti-drug antibody (ADA) response. Harmonization of reporting of NAb assay performance and results enables efficient communication and expedient review by industry and health authorities. Herein, a cross-industry group of NAb assay experts have harmonized NAb assay reporting recommendations and provided a bioanalytical report (BAR) submission editable template developed to facilitate agency filings. This document addresses key bioanalytical reporting gaps and provides a report structure for documenting clinical NAb assay performance and results. This publication focuses on the content and presentation of the NAb sample analysis report including essential elements such as the method, critical reagents and equipment, data analysis, study samples, and results. The interpretation of immunogenicity data, including the evaluation of the impact of NAb on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Pathogenicity and multigene sequence analysis reveal the widespread distribution of Alternaria alternata causing early blight in tomato - Omer Abassy; Alexander Balamurugan; Kuleshwar Prasad Sahu; Asharani Patel; Neelam Sheoran; Bhaskar Reddy; Robin Gogoi; Krishna Kumar Singh; Aundy Kumar (Journal of Plant Pathology, 2024)

A study on production of hydrogen using Al scrap feedstock - Robin Singh; Ramesh Kumar Guduru; Rakesh Kumar Vij (Environmental Science and Pollution Research, 2024)

Sesamol as a potent anticancer compound: from chemistry to cellular interactions - Ajay Kumar; Payal Bajaj; Brahmjot Singh; Kapil Paul; Pooja Sharma; Sukanya Mehra; Robin; Pardeep Kaur; Shivam Jasrotia; Parveen Kumar; Rajat; Vipourpreet Singh; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Unravelling the metabolomic pool of Ocimum microgreens under diverse growing conditions through targeted compound analysis and non-targeted UHPLC-QToF-IMS based approach - Arun Kumar; Narpinder Singh; Robin Joshi (Food Bioscience, 2024)

Ecosystem-scale insights into the dynamics of dissolved organic matter in an Asia's largest brackish water lagoon: Sources, fluxes, and biogeochemical significance - Vishnu Vardhan Kanuri; Pradipta Ranjan Muduli; R.S. Robin; Charan Kumar Basuri; Lovaraju Avvari; Sivaji Patra; G.V.M. Gupta; Nageswara Rao Gollapalli; B.R. Subramanian (Marine Pollution Bulletin, 2024)

Comparative evaluation of management modules against Maydis leaf blight disease in maize (Zea mays) - Sumit Kumar Aggarwal; K. S. Hooda; Harleen Kaur; Robin Gogoi; Prashant Chauhan; P. K. Bagaria; Pardeep Kumar; Mukesh Choudhary; Rahul Kumar Tiwari; Milan Kumar Lal (European Journal of Plant Pathology, 2024)

Determination of biogeochemical rate constants for Chilika Lake, a tropical brackish water lagoon on the east coast of India - Sivaji Patra; Charan Kumar Basuri; Pradipta R. Muduli; Vishnu Vardhan Kanuri; Robin R. S.; Ganguly Dipnarayan; Abhilash K. R.; Lovaraju Avvari; Uma Sankar Panda; Dash S. K.; Ramana Murthy M. V. (Frontiers in Marine Science, 2024)

Deciphering the metabolic signatures of Trigonella microgreens as a function of photoperiod and temperature using targeted compound analysis and non-targeted UHPLC-QTOF-IMS based approach - Arun Kumar; Narpinder Singh; Robin Joshi (Food Research International, 2024)

Volatile and aroma profiling of flower and rhizome of Hedychium flavescens growing in North Western Himalayan region - Kushal Kumar; Jigyasa Malhotra; Robin Joshi (Natural Product Research, 2023)

Anti-cancer Efficacy of Metformin: Recent Updates on Breast and Other Cancers - Md. Imtiazul Kabir; Robin Kumar; Lakshmi Sai Pratyusha Bugata; Komal Raina (Current Pharmacology Reports, 2023)

Harnessing cyanobacterium-fungal interactions to develop potting mixes for disease-free tomato nursery - Jyoti Shukla; Udita Gulia; Himani Gupta; Krati Gupta; Robin Gogoi; Arun Kumar; Himanshu Mahawar; Sekar Nishanth; Garima Saxena; Awani Kumar Singh; Lata Nain; Yashbir Singh Shivay; et al. (Phytoparasitica, 2023)

Unique Metabolic Shift Reveals Potential Mechanism of Cold and Freezing Acclimatization - Satyakam; Robin Joshi; Rajiv Kumar (Journal of Plant Growth Regulation, 2023)

Copper nanoparticles hold promise in the effective management of maize diseases without impairing environmental health - Lham Dorjee; Robin Gogoi; Deeba Kamil; Rajesh Kumar; Ankita Verma (Phytoparasitica, 2023)

Survey Outcome on Immunogenicity Risk Assessment Tools for Biotherapeutics: an Insight into Consensus on Methods, Application, and Utility in Drug Development - Jochem Gokemeijer; Yi Wen; Vibha Jawa; Shibani Mitra-Kaushik; Shan Chung; Alan Goggins; Seema Kumar; Kasper Lamberth; Karen Liao; Jennie Lill; Qui Phung; Robin Walsh; et al. (The AAPS Journal, 2023)

Sneak-peek into the chlorophyll content, antioxidant activity, targeted and non-targeted UHPLC-QTOF LC/MS metabolomic fingerprints of pulse microgreens grown under different photoperiod regimes - Arun Kumar; Narpinder Singh; Amritpal Kaur; Robin Joshi (Food Bioscience, 2023)

High dimensional model representation for flood fragility analysis of highway bridge - A. Anisha; Deepak Kumar Sahu; Pradip Sarkar; Sujith Mangalathu; Robin Davis (Engineering Structures, 2023)

Comparative quantification of dactylorhin among different wild tissues and in vitro cultures of Dactylorhiza hatagirea (D.Don) Soó, an endangered medicinal orchid of Western Himalayas - Archit Sood; Kanika Thakur; Robin Joshi; Dinesh Kumar; Ashish R Warghat (South African Journal of Botany, 2023)

Multiple traces of monkeypox detected in non-sewered wastewater with sparse sampling from a densely populated metropolitan area in Asia - Dhammika Leshan Wannigama; Mohan Amarasiri; Parichart Hongsing; Cameron Hurst; Charin Modchang; Sudarat Chadsuthi; Suparinthon Anupong; Phatthranit Phattharapornjaroen; Ali Hosseini Rad S.M.; Stefan Fernandez; Angkana T. Huang; Naris Kueakulpattana; et al. (Science of The Total Environment, 2023)

Comparative phytochemical analysis of Ferula assa-foetida with Ferula jaeschkeana and commercial oleo-gum resins using GC–MS and UHPLC-PDA-QTOF-IMS - Prithvi Pal Singh; Robin Joshi; Ravi Kumar; Ashok Kumar; Upendra Sharma (Food Research International, 2023)

Carbon dissipation from surgical cotton production wastewater using macroalgae, microalgae, and activated sludge microbes - Arun Robin Babu; Naresh Kumar Sharma; Matheswaran Manickam (Environmental Science and Pollution Research, 2022)

Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Fumigation by bacterial volatile 2, 5-dimethylpyrazine enhances anthracnose resistance and shelf life of mango - Archana T. Janamatti; Aundy Kumar; Charanjit Kaur; Robin Gogoi; Eldho Varghese; Sudhir Kumar (European Journal of Plant Pathology, 2022)

Iron induced qualitative enhancement in lipid profile of the cyanobacterium Anabaena sphaerica - Kikku Kunui; Robin Anigo Minj; Arun Kumar Mishra; Satya Shila Singh (Vegetos, 2022)

Multi-residue determination of pesticides in vegetables and assessment of human health risks in Western Himalayan region of India - Neelam Sharma; Atul Kumar; Siddhartha Singh; Suresh Kumar; Robin Joshi (Environmental Monitoring and Assessment, 2022)

Induction and submerged cultivation of Valeriana jatamansi adventitious root cultures for production of valerenic acids and its derivatives - Ashok Gehlot; Neha Chaudhary; Jyoti Devi; Robin Joshi; Dinesh Kumar; Shashi Bhushan (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Exemplifying endophytes of banana (Musa paradisiaca) for their potential role in growth stimulation and management of Fusarium oxysporum f. sp cubense causing panama wilt - Ajit kumar Savani; Ashok Bhattacharyya; Robin Chandra Boro; K. Dinesh; Nanjunda Swamy JC (Folia Microbiologica, 2021)

An enhanced deep image model for glaucoma diagnosis using feature-based detection in retinal fundus - Law Kumar Singh; Pooja; Hitendra Garg; Munish Khanna; Robin Singh Bhadoria (Medical & Biological Engineering & Computing, 2021)

Antifungal and defense elicitor activities of pyrazines identified in endophytic Pseudomonas putida BP25 against fungal blast incited by Magnaporthe oryzae in rice - Asharani Patel; Aundy Kumar; Neelam Sheoran; Mukesh Kumar; Kuleshwar Prasad Sahu; Prakash Ganeshan; Mushineni Ashajyothi; Subbaiyan Gopalakrishnan; Robin Gogoi (Journal of Plant Diseases and Protection, 2021)

Identification of host factors limiting the overexpression of recombinant Cu, Zn superoxide dismutase in Escherichia coli - Shweta Guleria; Robin Joshi; Dharam Singh; Sanjay Kumar (Biotechnology Letters, 2020)

In silico characterization and expression of disease-resistance-related genes within the collinear region of Brassica napus blackleg resistant locus LepR1′ in B. oleracea - Mostari Jahan Ferdous; Mohammad Rashed Hossain; Jong-In Park; Hoy-Taek Kim; Arif Hasan Khan Robin; Sathishkumar Natarajan; Manosh Kumar Biswas; Hee-Jeong Jung; Ill-Sup Nou (Journal of General Plant Pathology, 2020)

Detection of New Delhi Metallo-β-lactamase 1 and Cephalosporin Resistance Genes Among Carbapenem-Resistant Enterobacteriaceae in Water Bodies Adjacent to Hospitals in India - Sneha Girijan Kalasseril; Rahul Krishnan; Rejish Kumar Vattiringal; Robin Paul; Philip Mathew; Devika Pillai (Current Microbiology, 2020)

A rapid and sensitive method to detect SARS-CoV-2 virus using targeted-mass spectrometry - Praveen Singh; Rahul Chakraborty; Robin Marwal; V. S. Radhakrishan; Akash Kumar Bhaskar; Himanshu Vashisht; Mahesh S. Dhar; Shalini Pradhan; Gyan Ranjan; Mohamed Imran; Anurag Raj; Uma Sharma; et al. (Journal of Proteins and Proteomics, 2020)

Identifying archaeological evidence of past earthquakes in a contemporary disaster scenario: case studies of damage, resilience and risk reduction from the 2015 Gorkha Earthquake and past seismic events within the Kathmandu Valley UNESCO World Heritage Property (Nepal) - Christopher Davis; Robin Coningham; Kosh Prasad Acharya; Ram Bahadur Kunwar; Paolo Forlin; Kai Weise; Prem Nath Maskey; Anie Joshi; Ian Simpson; David Toll; Sean Wilkinson; Paul Hughes; et al. (Journal of Seismology, 2020)
The 2015 Gorkha Earthquake was a humanitarian disaster but also a cultural catastrophe that damaged and destroyed historic monuments across Nepal, including those within the Kathmandu Valley UNESCO World Heritage Property. In the rush to rebuild, traditionally constructed foundations are being removed and replaced with modern materials without assessments of whether these contributed to the collapse of a monument. Generally undertaken without scientific recording, these interventions have led to the irreversible destruction of earlier subsurface phases of cultural activity and the potential loss of evidence for successful traditional seismic adaptations and risk reduction strategies, with no research into whether modern materials, such as concrete and steel, would offer enhanced resilience. In response to this context, multidisciplinary post-disaster investigations were undertaken between 2015 and 2018, including archaeological excavation, geophysical survey, geoarchaeological analysis, linked to architectural and engineering studies, to begin to evaluate and assess the damage to, and seismic adaptations of, historic structures within Nepal’s Kathmandu Valley. Where possible, we draw on archaeoseismological approaches for the identification and classification of Earthquake Archaeological Effects (EAEs) at selected monuments damaged by the 2015 Gorkha Earthquake. Lessons learned from evidence of potential weaknesses, as well as historic ‘risk-sensitive tactics’ of hazard reduction within monuments, are now being incorporated into reconstruction and rehabilitation initiatives alongside the development of methods for the protection of heritage in the face of future earthquakes.

Differential modes of disease suppression elicited by silver nanoparticles alone and augmented with Calothrix elenkinii against leaf blight in tomato - Himanshu Mahawar; Radha Prasanna; Robin Gogoi; Awani Kumar Singh (European Journal of Plant Pathology, 2020)

Leaf stripping: an alternative strategy to manage banded leaf and sheath blight of maize - Harleen Kaur; Sanjay Kumar; K. S. Hooda; Robin Gogoi; Pravin Bagaria; R. P. Singh; Rakesh Mehra; Ashwani Kumar (Indian Phytopathology, 2020)

Experimental, numerical and field study investigating a heritage structure collapse after the 2015 Gorkha earthquake - Ashutosh Kumar; Paul N. Hughes; Vasilis Sarhosis; David Toll; Sean Wilkinson; Robin Coningham; Kosh Prasad Acharya; Kai Weise; Annie Joshi; Christopher Davis; Ram Bahadur Kunwar; Prem Nath Maskey (Natural Hazards, 2020)
This paper presents an investigation of the collapse of a 325-year-old multi-tiered heritage temple during the 2015 Gorkha earthquake in Kathmandu, Nepal. The research comprises a reconnaissance survey followed by a geotechnical investigation and numerical back-analysis carried out to understand the potential causes of the collapse. The assessment of the structural configuration of the temple indicated seismic vulnerability in the design due to the presence of discontinuous columns over the height of the temple and age-weakened bonding in the masonry walls. The geotechnical investigation revealed the presence of competent soil strata at the location, assisting the survey which indicated no differential or excessive settlement in the foundation. A series of cyclic triaxial tests were conducted on samples recovered during the geotechnical investigation to determine dynamic behaviour of the soil. Further, dynamic analysis of the plinth of the temple under the recorded acceleration–time history indicated a maximum drift percentage of 1.4% and residual relative displacement of 32 mm suggesting the potential reason behind the collapse. The output of this research will support seismic rehabilitation of ancient structures within World Heritage sites across Nepal and effective action plans to safeguard them against future earthquake hazard.

Regulation of color transition in purple tea (Camellia sinensis) - Manglesh Kumari; Shweta Thakur; Ajay Kumar; Robin Joshi; Prakash Kumar; Ravi Shankar; Rajiv Kumar (Planta, 2020)

Antimicrobial therapeutics delivery systems based on biodegradable polylactide/polylactide-co-glycolide particles - Robin Kumar; Divya Jha; Amulya K. Panda (Environmental Chemistry Letters, 2019)

Phenotypic and physiological characterization of maize inbred lines resistant and susceptible to maydis leaf blight - C. Manjunatha; Robin Gogoi; Bhupinder Singh; B. Jeevan; S. N. Rai; Pradeep Kumar Singh (Indian Phytopathology, 2019)

Assessment of resistance to rice tungro disease in popular rice varieties in India by introgression of a transgene against Rice tungro bacilliform virus - G. Kumar; M. Jyothsna; P. Valarmathi; S. Roy; A. Banerjee; J. Tarafdar; B. K. Senapati; S. Robin; S. Manonmani; R. Rabindran; I. Dasgupta (Archives of Virology, 2019)

Prunus cerasoides fruit extract ameliorates inflammatory stress by modulation of iNOS pathway and Th1/Th2 immune homeostasis in activated murine macrophages and lymphocytes - Anamika Sharma; Robin Joshi; Shiv Kumar; Rohit Sharma; Rajneesh; Yogendra Padwad; Mahesh Gupta (Inflammopharmacology, 2018)

Human Neural Stem Cell Extracellular Vesicles Improve Tissue and Functional Recovery in the Murine Thromboembolic Stroke Model - Robin L. Webb; Erin E. Kaiser; Shelley L. Scoville; Tyler A. Thompson; Sumbul Fatima; Chirayukumar Pandya; Karishma Sriram; Raymond L. Swetenburg; Kumar Vaibhav; Ali S. Arbab; Babak Baban; Krishnan M. Dhandapani; et al. (Translational Stroke Research, 2018)

Dental anomalies in pediatric patients with familial adenomatous polyposis - Seth Septer; Brenda Bohaty; Robin Onikul; Vandana Kumar; Karen B. Williams; Thomas M. Attard; Craig A. Friesen; Lynn Roosa Friesen (Familial Cancer, 2018)

Genome-wide characterization and stress-responsive expression profiling of MCM genes in Brassica oleracea and Brassica rapa - Ashokraj Shanmugam; Arif Hasan Khan Robin; Senthil Kumar Thamilarasan; Harshavardhanan Vijayakumar; Sathishkumar Natarajan; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Journal of Plant Biology, 2017)

Depth of soil compaction predominantly affects rice yield reduction by reproductive-stage drought at varietal screening sites in Bangladesh, India, and Nepal - Suresh Prasad Singh; Abhinav Jain; M. S. Anantha; Santosh Tripathi; Subarna Sharma; Santosh Kumar; Archana Prasad; Bhawana Sharma; Biswajit Karmakar; Rudra Bhattarai; Sankar Prasad Das; Shravan K. Singh; et al. (Plant and Soil, 2017)

When is a forest a forest? Forest concepts and definitions in the era of forest and landscape restoration - Robin L. Chazdon; Pedro H. S. Brancalion; Lars Laestadius; Aoife Bennett-Curry; Kathleen Buckingham; Chetan Kumar; Julian Moll-Rocek; Ima Célia Guimarães Vieira; Sarah Jane Wilson (Ambio, 2016)

Influence of suspended particulate matter on nutrient biogeochemistry of a tropical shallow lagoon, Chilika, India - Sivaji Patra; A. V. Raman; D. Ganguly; R. S. Robin; P. R. Muduli; VishnuVardhan Kanuri; K. R. Abhilash; B. Charan Kumar; B. R. Subramanian (Limnology, 2016)

Evaluation of virus resistance and agronomic performance of rice cultivar ASD 16 after transfer of transgene against Rice tungro bacilliform virus by backcross breeding - P. Valarmathi; G. Kumar; S. Robin; S. Manonmani; I. Dasgupta; R. Rabindran (Virus Genes, 2016)

Bioefficacy evaluation and dissipation pattern of nanoformulation versus commercial formulation of pyridalyl in tomato (Solanum lycopersicum) - Priya Saini; Madhuban Gopal; Rajesh Kumar; Robin Gogoi; Chitra Srivastava (Environmental Monitoring and Assessment, 2015)

Residue, dissipation, and safety evaluation of pyridalyl nanoformulation in Okra (Abelmoschus esculentus [L] Moench) - Priya Saini; Madhuban Gopal; Rajesh Kumar; Robin Gogoi (Environmental Monitoring and Assessment, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Refinement of schizophrenia GWAS loci using methylome-wide association data - Gaurav Kumar; Shaunna L. Clark; Joseph L. McClay; Andrey A. Shabalin; Daniel E. Adkins; Linying Xie; Robin Chan; Srilaxmi Nerella; Yunjung Kim; Patrick F. Sullivan; Christina M. Hultman; Patrik K. E. Magnusson; et al. (Human Genetics, 2015)

Osmotin-expressing transgenic tea plants have improved stress tolerance and are of higher quality - Amita Bhattacharya; Uksha Saini; Robin Joshi; Devinder Kaur; Awadhesh Kumar Pal; Nitish Kumar; Ashu Gulati; Prashant Mohanpuria; Sudesh Kumar Yadav; Sanjay Kumar; Paramvir Singh Ahuja (Transgenic Research, 2014)

In vitro cytotoxicity, antimicrobial, and metal-chelating activity of triterpene saponins from tea seed grown in Kangra valley, India - Robin Joshi; Swati Sood; Poonam Dogra; Madhvi Mahendru; Dharmesh Kumar; Shalika Bhangalia; Harish Chandra Pal; Neeraj Kumar; Shashi Bhushan; Arvind Gulati; Ajit Kumar Saxena; Ashu Gulati (Medicinal Chemistry Research, 2013)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Molecular characterization and delineation of subtle deletions in de novo “balanced” chromosomal rearrangements - Arun Kumar; Laurie A. Becker; Theresa W. Depinet; J. Marie Haren; C. Lisa Kurtz; Nathaniel H. Robin; Suzanne B. Cassidy; Daynna J. Wolff; S. Schwartz (Human Genetics, 1998)